Limitations of the Boston Carpal Tunnel Questionnaire in Assessing Severity in a Homogeneous Occupational Cohort - Venera Cristina Dinescu; Marius Bica; Ramona Constantina Vasile; Andrei Gresita; Bogdan Catalin; Alexandra Daniela Rotaru-Zavaleanu; Florentin Ananu Vreju; Lorena Sas; Marius Bunescu (Life)
Background: Carpal tunnel syndrome (CTS) is a common peripheral neuropathy, often assessed using the Boston Carpal Tunnel Questionnaire (BCTQ). The BCTQ evaluates symptom severity (SSS) and functional status (FSS) but has limitations in stratifying CTS severity, particularly in severe cases. Objective: This study aimed to evaluate the utility of the BCTQ in a homogeneous cohort of female workers engaged in repetitive manual tasks, exploring its correlation with objective clinical measures and its performance in detecting CTS severity. Methods: A cross-sectional study was conducted on 24 right-hand-dominant female workers with repetitive occupational tasks. CTS diagnosis was confirmed via clinical and electrodiagnostic criteria. Subjects completed the BCTQ, and correlations between BCTQ scores and objective measures such as median nerve cross-sectional area and nerve conduction studies were analyzed. Statistical analyses included comparisons across CTS severity groups and subgroup evaluations based on age and tenure. Results: The BCTQ demonstrated moderate correlations with objective measures, with a strong correlation between SSS and FSS scores (r = 0.86, p < 0.001). However, the sensitivity of the SSS and FSS was limited, particularly for severe CTS cases. Paradoxically lower scores in severe cases may reflect questionnaire limitations or adaptive responses. Targeted questions addressing pain and sensory symptoms showed better sensitivity (>80%) and may guide clinicians in identifying slight CTS cases. Conclusions: While the BCTQ remains a valuable tool for assessing CTS, its limitations necessitate complementary use of objective diagnostic tools, particularly for severe cases. Future refinements, such as tailored scoring systems and integration with clinical measures, could enhance its diagnostic utility and ensure comprehensive assessment of CTS severity.